1942
DOI: 10.1084/jem.75.5.495
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response of Human Beings Following Vaccination With Influenza Viruses

Abstract: Eleven different preparations of influenza virus were used to vaccinate large groups of human beings. The antibody response to these vaccines was measured by means of the in vitro agglutination inhibition test, and the geometric mean titers of sera taken 2 weeks after vaccination were compared. From these comparisons the following conclusions were drawn: 1. There was a wide individual variation in the antibody response of human beings to the same preparation of influenza virus administrated subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1942
1942
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…When this was not feasible, the antibody levels in single convalescent sera were determined. While too great diagnostic significance cannot be attached to the results obtained with a single serum, certain ranges of antibody levels have been reported for apparently normal individuals (31). Therefore, one can say that the titers are within the normal limits and that the patient probably had not had a recent infection, or that the antibody level for one of the viruses is distinctly elevated and that the patient may have had contact with this virus within the last few months.…”
mentioning
confidence: 99%
“…When this was not feasible, the antibody levels in single convalescent sera were determined. While too great diagnostic significance cannot be attached to the results obtained with a single serum, certain ranges of antibody levels have been reported for apparently normal individuals (31). Therefore, one can say that the titers are within the normal limits and that the patient probably had not had a recent infection, or that the antibody level for one of the viruses is distinctly elevated and that the patient may have had contact with this virus within the last few months.…”
mentioning
confidence: 99%
“…After Hirst et al1 had demonstrated that higher vaccine doses could induce higher levels of serum antibody and that vaccine dose could be measured by an in vitro assay based on agglutination of chicken erythrocytes,2 the scene was set for more effective and consistent vaccine production. The in vitro assay was further standardised by the development of the chick cell agglutination (CCA) assay3 and the use of an International Standard for haemagglutination,4 but still there were problems.…”
Section: Early Days Of Influenza Vaccinesmentioning
confidence: 99%
“…Tenfold higher concentrations of antigen increased antibody response by 20%, and further sixfold increases failed to result in greater antibody response. There is also evidence for wide interindividual variability in antibody response post vaccination . Of note, more recent studies demonstrate that higher doses of antigen may provoke a greater antibody response .…”
Section: Epidemiology Of Influenza and Prevention By Vaccinesmentioning
confidence: 99%